2015
DOI: 10.1016/j.cmet.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress and Angiogenesis

Abstract: Proper tissue vascularization is vital for cellular function as it delivers oxygen, nutrients, hormones, and immune cells and helps to clear cellular debris and metabolic waste products. Tissue angiogenesis occurs to satisfy energy requirements and cellular sensors of metabolic imbalance coordinate vessel growth. In this regard, the classical pathways of the unfolded protein response activated under conditions of ER stress have recently been described to generate angiomodulatory or angiostatic signals. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
142
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 164 publications
5
142
1
2
Order By: Relevance
“…1). However, chronic or overwhelming ER-stress elicits apoptotic signals such as CHOP expression followed by an activation of intrinsic mitochondrial apoptotic pathway (18,37). In this study, we observed that NSC produced a dose-and timedependent elevation of GRP78, XBP1s and CHOP mRNAs (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…1). However, chronic or overwhelming ER-stress elicits apoptotic signals such as CHOP expression followed by an activation of intrinsic mitochondrial apoptotic pathway (18,37). In this study, we observed that NSC produced a dose-and timedependent elevation of GRP78, XBP1s and CHOP mRNAs (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…When PERK is activated, it phosphorylates eukaryotic translation-initiation factor 2α (eIF2α), reducing mRNA translation and biosynthetic protein-folding load in the ER. Once IRE1α is activated, it functions as an endoribonuclease to remove a 26-nucleotide region from unspliced X-box binding protein 1 (XBP1u) mRNA, generating a spliced XBP1 (XBP1s) mRNA that yields an active transcription factor (XBP1s) to regulate the expression of various subsets of genes involved in protein folding (18,38). On the other hand, the activated IRE1α causes a degradation of selective mRNAs, resulting in an overall decrease in protein biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, CHOP has the propensity to drive apoptosis [51] and thus cells might be led to apoptosis. Our linear regression analysis showed that the expression level of p-eIF2α was positively associated with the number of bone-forming osteoblasts, and negatively associated with that of bone-resorbing osteoclasts.…”
Section: Discussionmentioning
confidence: 99%